2013
DOI: 10.1603/an12074
|View full text |Cite
|
Sign up to set email alerts
|

The Geographic Distribution of Rhagoletis pomonella (Diptera: Tephritidae) in the Western United States: Introduced Species or Native Population?

Abstract: ABSTBACT The apple maggot fly, Rhagoletis pomonella Walsh (Diptera: Tephritidae), is a major pest of commercially grown domesticated apple (Malus domestica Borkhausen) in North America. The shift of the fly from its native host hawthorn (Crataegus mollis) to apple in the eastern United States is often cited as an example of incipient sympatric speciation in action. However, R. pomonella is also present in the Pacific Northwest region of the United States where it infests apple, native black hawt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…Similarly, R. pomonella is rare in black hawthorn in central Washington State and patchily distributed in the plant elsewhere throughout the northwestern U.S. (Yee 2008). The same also appears to be true throughout most of the western U.S., supporting the contention that R. pomonella was introduced to the region and is not native (Hood et al 2013). It remains unclear if black hawthorn fruit is unsuitable for sustaining high fl y densities or whether environmental conditions where black hawthorns thrive, in combination with the plant's fruiting phenology, are not optimal for R. pomonella survival.…”
Section: R Tabelllariamentioning
confidence: 64%
See 2 more Smart Citations
“…Similarly, R. pomonella is rare in black hawthorn in central Washington State and patchily distributed in the plant elsewhere throughout the northwestern U.S. (Yee 2008). The same also appears to be true throughout most of the western U.S., supporting the contention that R. pomonella was introduced to the region and is not native (Hood et al 2013). It remains unclear if black hawthorn fruit is unsuitable for sustaining high fl y densities or whether environmental conditions where black hawthorns thrive, in combination with the plant's fruiting phenology, are not optimal for R. pomonella survival.…”
Section: R Tabelllariamentioning
confidence: 64%
“…Rhagoletis pomonella was likely introduced from eastern North America into the western U.S. in the 1950s or 1970s (AliNiazee & Westcott 1986). In the western U.S., R. pomonella is found in Idaho, Washington, Oregon, Utah, Colorado, and California (Brunner 1987, Dowell 1989, Yee & Goughnour 2008, Hood et al 2013), but its presence in Montana has never been confi rmed. A recent survey conducted by Hood et al (2013) found the fl y absent from fi ve sites in three counties (Gallatin, Missoula, and Mineral) in southwestern and west-central Montana.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Populations in Mè xico (below) may also be native. Populations in the western United States are almost certainly introduced (Dowell 1991, Hood et al 2013, likely from the eastern United States.…”
Section: Apple Maggot Rhagoletis Pomonella (Walsh)mentioning
confidence: 99%
“…Berlocher and Enquist (1993), Berlocher and McPheron (1996), Powell (2012), Hood et al (2013) High -C. monogyna Jacq.…”
Section: Apple Maggot Rhagoletis Pomonella (Walsh)mentioning
confidence: 99%